Making law in the United States Courts of Appeals - Klein, David E., 1970- (Cambridge University Press, 2002)
This book asks how federal court judges decide cases when faced with unsettled law issues. Are their decisions influenced by higher court judges or other judges at their same level? Statistical analyses and interviews with judges determine that judges give attention to colleagues, but demonstrate independence from the Supreme Court.